2010
DOI: 10.3171/2010.2.focus1036
|View full text |Cite
|
Sign up to set email alerts
|

Can surgery improve neurological function in penetrating spinal injury? A review of the military and civilian literature and treatment recommendations for military neurosurgeons

Abstract: Neurosurg Focus 28 (5):E4, 20101 P atients with PSIs present very complex, multidisciplinary management challenges for military surgeons. Not only can the patient have immediate and delayed life-threatening damage to organs along the path of the projectile, the spinal column and possibly the neurological structures contained within can also, by definition, suffer injury, the severity of which depends on multiple factors. Spinal cord injury from spinal GSWs is more often a complete lesion with a decreased poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 48 publications
(64 reference statements)
1
55
0
2
Order By: Relevance
“…[5][6][7] Most studies have failed to demonstrate a clear benefi t of decompression for neurological outcome, instead frequently fi nding increased complication rates with operative intervention. [8][9][10][11][12][13] However, a large longitudinal clinical series evaluating the effectiveness of this shift toward nonoperative treatment has not been published.…”
mentioning
confidence: 97%
“…[5][6][7] Most studies have failed to demonstrate a clear benefi t of decompression for neurological outcome, instead frequently fi nding increased complication rates with operative intervention. [8][9][10][11][12][13] However, a large longitudinal clinical series evaluating the effectiveness of this shift toward nonoperative treatment has not been published.…”
mentioning
confidence: 97%
“…Pressure or shock waves created by the bullet impacting on adjacent tissue and temporary cavitation may be responsible for this kind of injury in the battlefields. 7,8 Unlike military gunshot injuries, blast effect may have a limited role in neurological injury in civilian GSIS. 9 This is supported by our findings.…”
Section: Discussionmentioning
confidence: 98%
“…The routine use of a cervical collar could cause detrimental side effects, such as airway obstruction or masking life-threatening wounds on patients with penetrating injury to the neck. 6,7 In our series, the use of external bracing was influenced by individual surgeon preference. However, in retrospect, we found that the factors having a statistically significant association with physician's recommendation to brace were the same factors that were significant on the incidence of paralysis (that is, multiple vertebral levels of damage and presence of a fragment in the canal).…”
Section: Discussionmentioning
confidence: 98%
“…A trend was noted toward surgical management of lumbar or cauda equina injuries and nonsurgical/ observation of complete injuries. 7,14,17,18 CONCLUSION CCS is a common presentation in patients with spinal cord injury, although not commonly seen in patients who suffered GSW to the spine. Some suggested algorithms exist regarding the management of these patients, but still cases should be individualized depending on the specific nature of their presentation.…”
Section: Nonsurgicalmentioning
confidence: 99%
“…14 Spinal instability can be present in any abnormal angulation or translation and in cases where the bullet traverses the pedicle or the facet. 7,14,17 Progressive neurological deficit, cerebrospinal fluid leak and evidence of lead toxicity are also complications in which surgical intervention is strongly recommended. Level of lesion (cervical, thoracic and lumbar), severity of injury, or the presence Figure 2.…”
Section: Nonsurgicalmentioning
confidence: 99%